2015
DOI: 10.2355/isijinternational.isijint-2015-118
|View full text |Cite
|
Sign up to set email alerts
|

Metal/Slag Separation Behavior of CCA with Various Slag Systems and Effect of Slag Composition on the Content of Sulfur and Phosphorus in Iron Nugget

Abstract: The smelting reduction of high Al2O3 ores with petroleum coke containing various slags was investigated in the temperature range of 1 673 to 1 773 K with a special focus on the effect of slag composition on the desulfurization and dephosphorization of iron nugget. The efficient smelting reduction of the carbon composite agglomerate (CCA) would greatly be affected by the mineralogy of iron ore, coal and additives used in the preparation of CCA although the design of final slag composition is important for the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This is because the melting point of the slag is lowered by adding CaO. 22) Considering that the carburization of iron proceeds in the molten slag as explained by Kim et al, 4) it is necessary to examine the slag composition in the initial melting stage of iron. Figures 10 and 11 show the SEM images of the crosssection of the samples of the groups A and B after heated up to 1 200°C, respectively.…”
Section: Carburization Behaviormentioning
confidence: 99%
“…This is because the melting point of the slag is lowered by adding CaO. 22) Considering that the carburization of iron proceeds in the molten slag as explained by Kim et al, 4) it is necessary to examine the slag composition in the initial melting stage of iron. Figures 10 and 11 show the SEM images of the crosssection of the samples of the groups A and B after heated up to 1 200°C, respectively.…”
Section: Carburization Behaviormentioning
confidence: 99%
“…5) Park et al measured the P distribution between iron nuggets and CaO-Al 2 O 3 system slag when high-alumina iron ore was melt-reduced in the temperature range of 1 673-1 773 K. They reported that the high-basicity oxides of the CaO-Al 2 O 3 system can suppress the distribution of P in iron, but the oxide phase particles must be separated. 6) As described above, in the temperature range in which iron exists as a solid and in a high oxygen partial pressure environment, it is possible to suppress the reduction of P and concentrate it in the oxide phase. In contrast, the current steelmaking process uses a high-basicity slag (C/S > 2.0) to achieve a high-efficiency and high-speed dephosphorization operation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the separation behaviour has often been studied as a key factor for control over the reaction in the pellet. [15][16][17][18][19][20][21][22][23][24][25][26] Matsumura et al 15) reported reduction behaviour of the self-reducing pellet during heating up to 1 500°C which reproduced the rotary hearth furnace condition. This report concluded that the iron melting due to the carburization reaction is the dominant controlling factor for the iron-slag separation.…”
Section: Introductionmentioning
confidence: 99%
“…J. O. Park et al 21,22) reported the effect of CaO addition as one of the counter measures for the high Al 2 O 3containing iron ore. They concluded that the reduction of the pellet with a highly basic slag with a low SiO 2 content slowed the slag melting, resulting in a delayed separation of metal and slag.…”
Section: Introductionmentioning
confidence: 99%